Episodic synchronization in dynamically driven neurons - Balenzuela, Pablo (2006)
We examine the response of type II excitable neurons to trains of synaptic pulses, as a function of the pulse frequency and amplitude. Similarly to the case of harmonic inputs, these neurons exhibit a resonant behavior also for pulsed inputs. We interpret this phenomenon in terms of the subthreshold response of the neuron. In the presence of dynamical trains of input pulses whose frequency varies continuously in time, the receiving neuron synchronizes episodically to the input pulses, whenever the pulse frequency lies within the neuron's locking range. The results are obtained both in numerical simulations of the Morris-Lecar model and in an electronic implementation of the FitzHugh-Nagumo system, evidencing the robustness of the phenomenon. © 2006 The American Physical Society.